PERAN GURU DALAM MENINGKATKAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI SISWA KELAS IV SD - Ichsanurrahmah, Dina; Cecep Maman Hermawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the teacher's role in improving the descriptive essay writing ability of fourth-grade elementary school students and identify supporting and inhibiting factors. A qualitative approach with a case study design was employed, involving one classroom teacher and six students as subjects. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results showed that the teacher carried out five integrated roles: as a learning planner, as a model and example giver, as a scaffolder, as a constructive feedback provider, and as a creator of a supportive literacy environment. Supporting factors included student enthusiasm, availability of varied media, and teacher patience, while inhibiting factors were time limitations and diversity of student abilities. The study concludes that a systematic and sustainable teacher role effectively improves descriptive writing skills.